Representation of the Swine Sign as a Signifier of Purification in Ibanese Entelah - Ganing, Patricia; Amat, Asmiaty; Abdul Samad, Lokman (Melayu: Jurnal Antarabangsa Dunia Melayu, 2018)
Entelah or riddles are a part of the oral literature of the Iban. Entelah contain many signs for different signified meanings. A study of 10 entelah reveals that the most dominant sign is that of 'swine' or 'pig'. Consequently, this study employs the semiotic theory of Charles Sander Peirce to study the use of 'swine' or 'pig' as sign, signifier and signified among the Iban community. The findings show that swine are not only consumed but are also a used in purification rituals to remove the badi (bad influence) or sial (ill fortune) asscoiated with deaths, taboo marriages, out-of-wedlock births, adulterers, and the purification of agricultural lands. Keywords: Entelah , swine/pig, purification signifiers, Peirce's semiotic theory, Iban community